NEXUS Gains in the Indus Basin: Pakistan - CGIAR Initiative on NEXUS Gains (International Water Management Institute, 2024)
A NEXUS Gains transboundary river basin brief shares examples of the Initiative’s work across five work packages in the Indus Basin in Pakistan.